DETERMINANTS OF INJURY IN AGRICULTURAL AREA - Arista Maisyaroh; Eko Prasetya Widianto; Rizeki Dwi Fibriansari (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Nearly half of the world's population lives in rural areas where agriculture is the primary source of livelihood (FAO, 2013). Many factors affect the health of agricultural workers, and improving the health of this population will require a variety of approaches. Farmers can experience various diseases and chronic diseases similar to the general population; however, there is evidence that they are at higher risk for acute injuries due to work, certain chronic diseases, and pesticide diseases. Objectives: This study aims to analyze the factors causing injury in the area of Agriculture. Methods: This study adopted a cross-sectional explanatory method. The variable consists of several factors that cause injury, namely, vulnerability, threat factors, and ability factors. The population consists of farmers who are members of farmer groups under the assistance of the Lumajang District Agriculture Office. The participants were recruited using multi-step sampling steps with 354 respondents. Data were collected using a questionnaire, which was then analyzed using Structural Equation Modelling (SEM) variance base Partial Least Squares (PLS) Results: By using the PLS-3 program, the effect of susceptibility factor on injury events is 0.487, and the effect of susceptibility factor on injury events through threat factor is 0.107 so that the total impact of susceptibility factor on injury events is 0.595, the impact of ability factor on injury events is 0.286. The influence of susceptibility factor to injury events through the threat factor is 0.063, so the total impact of the ability factor on injury events is 0, 349. While the threat factor only increases by 21.9% of injury events. So, it can be concluded that the vulnerability factor is the highest factor increasing the incidence of injury by 59.5% compared to other factors. Conclusion: The development of a injury prevention model can be done by reducing the vulnerability of farmers by limiting working hours in agricultural areas, paying attention to nutrition and fluid intake, controlling accompanying diseases, and facilitating insurance for farmers.